1-Isopropenyl-1H-1,3-benzimidazol-2(3H)-one - Saber, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title N-substituted benzimidazol-2-one, C(10)H(10)N(2)O, the fused ring system is almost planar (r.m.s. deviation = 0.01 angstrom) and aligned at 57.9 (1)degrees with respect to the propenyl fragment. In the crystal, adjacent molecules are linked by pairs of N-H center dot center dot center dot O hydrogen bonds into inversion dimers.